An?lise filogen?tica do g?nero de vespas sociais Neotropical Chartergellus Bequaert, 1938 (Hymenoptera: Vespidae: Polistine: Epiponini) - Daza Gongora, Mario Nicolas (2023)
Within the social wasps, the tribe Epiponini (Polistinae) has the highest number of genera recorded in the neotropical region. The genus Chartergellus Bequaert, 1938, comprises 12 species occurring from the northern region of Costa Rica to southeastern Brazil. Since the last revision, five new species have been described, and there has been no update to the identification key. In the present study, the monophyly of Chartergellus is tested, and a relationship among the species of the genus is presented, along with an updated identification key, including the five recently described species. Phylogenetic analyses were employed using parsimony criteria, based on morphological data nest architecture and male genitalia. A matrix with 19 terminal taxa and 57 characters was obtained. The phylogenetic analysis resulted in a single tree topology, with 185 steps, consistency index (CI) 0,48 and retention index (RI) 0,61: ((C. jeannei + (C. amazonicus + (C. afoveatus + C. zucchi))) + ((C. atectus + C. nigerrimus) + ((C. communis + C. punctactior) + ((C. flavoscutellatus + C. zonatus) + (C. sanctus + C. golfitensis))))). In general, the recovered clades are in agreement with previous literature, and the genus showed a high level of support. In Appendix B, the new synonymy between Chartergellus trinitatis and Pseudopolybia compressa de Saussure, 1854, is presented due to the palpal-labial formula (6-4) and the presence of a dorsal sulcus on the mesopleura.